SLR STUDY: CULTIVATING ECOLOGICAL AWARENESS THROUGH PROJECT-BASED SCIENCE LEARNING - Isma Azizah, Faiqotul; Saihan , Saihan; Mu'alimin, Mu'alimin (Program Studi PGMI, 2025)
This study aims to explore the effectiveness of project-based science and social science (IPAS) learning in instilling ecological awareness from an early age. The focus of the study is to understand how the project-based learning approach can improve students' understanding of environmental conservation and identify challenges and supporting factors in its implementation. This study uses a library research method with a qualitative approach. Data were collected from primary and secondary sources such as scientific journals, textbooks, research reports, and curriculum documents. Data analysis was carried out through literature studies, content analysis, and triangulation to ensure the accuracy of the findings. The research process includes source collection, document selection, data extraction, and information synthesis. The results of the study indicate that project-based science and social science learning is effective in improving students' ecological awareness through practical activities such as tree planting, recycling, and environmental observation. However, its implementation faces obstacles such as lack of resources, teacher training, and integration with the curriculum. Educators have mixed views, with some supporting this approach because it is considered contextual, while others complain about the lack of support. In addition, there were protests from the community who considered project activities to interfere with academic focus. Student academic outcomes also varied, with some schools reporting significant improvements, while others showed no significant changes. In conclusion, project-based learning has great potential to increase ecological awareness, but its success depends on the support of teachers, schools, and communities, as well as good integration with the cycle.